Effect of austempering temperature on microstructure and mechanical properties of ductile cast iron modified by niobium - Sckudlarek W.* (2021)
© 2021 The Authors.Owing to their exceptional physical, mechanical, and technological properties, ductile cast irons have been increasingly used, especially in automotive industries. Alloying elements and heat treatment routes can increase the strength of ductile irons. In this work, the effects of austempering temperature and time on the microstructure and mechanical properties of a ductile cast iron modified by 0.35% Nb have been studied. Two austempering temperatures of 320 °C and 360 °C for a holding time of 15, 30, 60, and 90 min were applied. The niobium addition was found to be effective in homogenizing the size and distribution of graphite nodules, maintaining the degree of nodularization above 90%, favoring pearlite refining, increasing the volume fraction of pearlite, forming niobium carbides in dispersed blocks in the matrix and graphite nodules, increasing both the yield and tensile strength, and reducing the elongation. Both the niobium addition and austempering temperature improved the yield and tensile strength but decreased the elongation compared to those of the reference ductile iron. The best combination of strength and ductility was observed at an austempering time of 60 min. The effect of austempering temperature on the microstructure and tensile mechanical properties of tested irons was found to be crucial.